The Priority Of The Principle Of Justice Over The Principle Of Benefit And The Principle Of Legal Certainty - Diah Ratu Sari (SEAN Institute, 2025)
As a state of law, law enforcement officers in Indonesia, including the police, prosecutors and judges, are always trying to solve problems that occur legally. In practice, law enforcement officers, especially judges, when going to make their decisions must be careful and wise in prioritizing the principle of justice or the principle of expediency or the principle of legal certainty. Usually judges choose to prioritize the principle of justice so that a fair decision is produced as stated at the top of a court decision: For the sake of Justice Based on God Almighty. Article 53 paragraph (2) of the Criminal Code provides guidelines for punishment that if in upholding law and justice as referred to in paragraph (1) there is a conflict between legal certainty and justice, the judge must prioritize justice. This study wants to find out which principles are prioritized in law enforcement: the principle of justice, the principle of expediency or the principle of legal certainty and what reasons judges prioritize the principle of justice. The research method used is normative research using primary and secondary legal materials. Legal materials were obtained through literature study and then analyzed qualitatively. After doing research, it is concluded that the principle that needs to be prioritized in law enforcement is the principle of justice. The reason is because the main goal of justice seekers is to obtain justice rather than benefits and legal certainty.